Three new species of Salacioideae (Celastraceae) - Lombardi, Julio Antonio [UNESP] (Wiley-Blackwell, 2010)
This paper describes three new species of Salacioideae Cheiloclinium and Salacia (Celastraceae) from South America: C. brevipetiolatum Lombardi is characterized by its very short, only 5mm long petioles; S. krigsneri Lombardi is distinguished by its dichasium (inflorescence) with shortened lateral branches, a unique feature among neotropical species; and S. vernicosa Lombardi can be discerned from other species by its fascicled inflorescences and large leaves, dried inflorescence covered with resinous substance, tubuliform flowers, flat, ring-shaped disc, and berries with ribs at base and lobes at apex.